Starting off on the right foot: Language learning classes and the educational success of immigrant children - Lisa Sofie Höckel; Pia Schilling (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
This study is the first empirical analysis to identify the causal effect of a separate preparatory language learning class on the academic success of newly immigrated primary school-aged children in comparison to their direct integration into regular classrooms. Employing unique administrative panel data from the German federal state Hamburg between 2013 and 2019, we use the quasi-random allocation of refugee children to neighborhoods and therewith schools to measure the effect of the two educational integration models on standardized test scores and the probability of attending an academic track in secondary school. Our results show that primary school-aged refugees who visit a preparatory class perform significantly worse in standardized test scores in fifth grade. The negative effect is particularly strong for Math and German. They further have a slightly lower probability to attend the academic track. Overall, our results indicate that integrating newly immigrated children directly into regular classrooms fosters their academic achievement more than schooling them first in preparatory classes with a focus on language learning. – – Die vorliegende Studie untersucht den kausalen Effekt einer separaten Vorbereitungsklasse (Willkommensklasse) auf den akademischen Erfolg von neu zugewanderten Kindern im Grundschulalter. Auf Grundlage administrativer Individualdaten aus Hamburg zwischen 2013 und 2019 nutzen wir die quasi-zufällige Zuweisung von Geflüchteten in Stadtteile und damit von geflüchteten Kindern in Schulen, um den Effekt der Vorbereitungsklasse auf den Spracherwerb und die Wahrscheinlichkeit eines Gymnasiumbesuchs zu messen. Unsere Ergebnisse zeigen, dass geflüchtete Kinder, die eine Vorbereitungsklasse besuchen, im Vergleich zu geflüchteten Kindern, die direkt in eine Regelklasse integriert werden, bei standardisierten Tests in der fünften Klasse deutlich schlechter abschneiden. Der negative Effekt ist besonders stark für die Fächer Mathematik und Deutsch. Außerdem haben die Schülerinnen und Schüler eine etwas geringere Wahrscheinlichkeit ein Gymnasium zu besuchen. Insgesamt deuten unsere Ergebnisse darauf hin, dass die direkte Integration von neu zugewanderten Kindern in Regelklassen ihre schulischen Leistungen stärker fördert als der Besuch von Vorbereitungsklassen mit intensivem Deutschunterricht.
Keywords: I24; I21; J13; J15; 330; Academic achievement; education economics; language skills; migration; integration policy